A prospective study for evaluation of Alvarado score in diagnosis of acute appendicitis - Kapadia, Navneetkumar M.; Rangwala, Varin; Rathod, Jignesh B.; Bhatt, Ravi; Patel, Sujan R. (International Surgery Journal, 2022)
Background: Acute appendicitis is a common cause of abdominal pain for which a prompt diagnosis is rewarded by a decrease in morbidity and mortality. Delay in the diagnosis will lead to an increased morbidity and mortality rate, on another hand overzealous diagnosis may lead to increased negative appendectomy rates. Notwithstanding advances in modern radiographic imaging and diagnostic laboratory investigations, the diagnosis of appendicitis remains essentially clinical. To decrease the negative appendectomy rate and to increase the positive diagnostic rate of appendicitis, various scoring systems were designed. Alvarado score is one of them. Methods: A total of 100 operated cases of appendicectomy were studied. Their clinical diagnosis, assessed by the Alvarado scoring is compared with radiological and histopathological diagnoses, to obtain the sensitivity and specificity of the Alvarado score system. NPV, PPV, and percentages of various demographic and clinical data were calculated accordingly. Results: In this study, the positive predictive value of Alvarado scoring is found to be high i.e.; patients will have a high chance of acute appendicitis. On the other hand, the negative predictive value is low. Sensitivity for Alvarado’s score is 50% while specificity is 88.9%. Conclusions: In this study, we concluded that the Alvarado score has a very high positive predictive value i.e.; diagnostic accuracy. Also with the help of the Alvarado score, we can reduce the number of negative appendicectomies.